2013
DOI: 10.1155/2013/861691
|View full text |Cite
|
Sign up to set email alerts
|

Hardware Acceleration of Beamforming in a UWB Imaging Unit for Breast Cancer Detection

Abstract: The Ultrawideband (UWB) imaging technique for breast cancer detection is based on the fact that cancerous cells have different dielectric characteristics than healthy tissues. When a UWB pulse in the microwave range strikes a cancerous region, the reflected signal is more intense than the backscatter originating from the surrounding fat tissue. A UWB imaging system consists of transmitters, receivers, and antennas for the RF part, and of a digital back-end for processing the received signals. In this paper w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Filtering also compensates path-length dependent Listing 1: MIST Beamforming computational kernel. A discussion on the determination of the parameters in capital letters can be found in the literature [3], [4]. MUSIC-Inspired Reconstruction.…”
Section: MI Breast-cancer Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Filtering also compensates path-length dependent Listing 1: MIST Beamforming computational kernel. A discussion on the determination of the parameters in capital letters can be found in the literature [3], [4]. MUSIC-Inspired Reconstruction.…”
Section: MI Breast-cancer Detectionmentioning
confidence: 99%
“…Profiling. Previous work on the hardware acceleration of MIST showed that filter weights and alignment delays can be computed offline once the system has been characterized and that the air-skin clutter removal step can be implemented sufficiently fast in software [6], [4]. Consequently, we focused our effort on accelerating the beamforming step (Listing 1).…”
Section: Hardware Architecturementioning
confidence: 99%
“…The effects of the impairments on the receiver performance are characterized in terms of the overall detection system performance, in other words, imaging quality which is specified by visual inspection of the energy maps reconstructed by imaging algorithm [59] [33] and SMR/SCR. As defined in Chapter 2, the tumor can be detected if and only if SMR and SCR are greater than 10 dB and 0 dB, an energy peak appears at the correct tumor position.…”
Section: Parammentioning
confidence: 99%